2013
DOI: 10.1242/jeb.080945
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyanin with phenoloxidase activity in the chitin matrix of the crayfish gastrolith

Abstract: SUMMARYGastroliths are transient extracellular calcium deposits formed by the crayfish Cherax quadricarinatus von Martens on both sides of the stomach wall during pre-molt. Gastroliths are made of a rigid chitinous organic matrix, constructed as sclerotized chitin-protein microfibrils within which calcium carbonate is deposited. Although gastroliths share many characteristics with the exoskeleton, they are simpler in structure and relatively homogeneous in composition, making them an excellent cuticle-like mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 40 publications
(42 reference statements)
0
39
0
Order By: Relevance
“…Some of them include, in addition to the carbohydrate esterase 4 CDA-like 1 domain identified here, the chitin-binding peritrophin A domain (CBM; Pfam ID PF01607) and/or the low density lipoprotein (LDL) receptor domain class A (Pfam ID PF00057). The sequences of these 10 transcripts are found in TSA GADE01000000 (Glazer et al, 2013) and TSA GAFS01000000 , and are also characterized at the bottom of supplementary material Table S1 here. A division of the CDAs may be done on a putative functional basis, namely, determining the contigs that contain the essential aspartic acid residue in motif 1 and the two histidine residues in motif 2, as described by Dixit et al (Dixit et al, 2008).…”
Section: Chitin Deacetylasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them include, in addition to the carbohydrate esterase 4 CDA-like 1 domain identified here, the chitin-binding peritrophin A domain (CBM; Pfam ID PF01607) and/or the low density lipoprotein (LDL) receptor domain class A (Pfam ID PF00057). The sequences of these 10 transcripts are found in TSA GADE01000000 (Glazer et al, 2013) and TSA GAFS01000000 , and are also characterized at the bottom of supplementary material Table S1 here. A division of the CDAs may be done on a putative functional basis, namely, determining the contigs that contain the essential aspartic acid residue in motif 1 and the two histidine residues in motif 2, as described by Dixit et al (Dixit et al, 2008).…”
Section: Chitin Deacetylasesmentioning
confidence: 99%
“…The structural proteins and the enzymes responsible for the partial degradation of the old cuticle and the construction of the new one are synthesized in, or transported through the underlying hypodermis, which is composed mainly of epithelial cells supported by structural and storage connective tissues (Glazer et al, 2013;Johnson, 1980;Roer and Dillaman, 1984). The cuticle is composed of four layers ordered: epicuticle, exocuticle, endocuticle and membranous layer (Roer and Dillaman, 1984;Skinner, 1985;Travis, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial staining showed that the ROS was largely distinct from the bacteria and from features of the barnacle. We hypothesize that these ROS at the cuticle layers also contribute to oxidative crosslinking (Okay et al, 1995;Dijkgraaf et al, 2003;Lattuada et al, 2013), as seen in other crustaceans (Willis, 1999;Glazer et al, 2013), and are critical to cuticle development and hardening, as seen in insects (Hopkins and Kramer, 1992;Suderman et al, 2006;Andersen, 2010). Further work is needed to define the specific ROS present and show the extent of their presence during development as only post-metamorphic juveniles were examined.…”
Section: Discussionmentioning
confidence: 99%
“…Arthropod cuticle is not solely a physical barrier to the environment but can contribute to critical processes such as immune responses and cross-linking for cuticle hardening and calcification of exoskeleton (Ashida and Brey, 1995;Sugumaran and Nelson, 1998;Adachi et al, 2005;Suderman et al, 2006;Glazer et al, 2013). In crustaceans, cuticle tearing leaks hemolymph and releases proteins, which coagulate sealing the wound and preventing infection (Iwanaga et al, 1998;Li et al, 2002;Jiravanichpaisal et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In silico confirmation of Cq-M15 sequence and transcription pattern Reference C. quadricarinatus transcriptome was constructed from sequencing of four sets of samples as described previously (Tynyakov et al, 2015): (1) RNA extracted from hypodermis-, gastrolith-and molarforming epithelium sequenced by 100 bp paired-end sequencing (Illumina HiSeq2000, USA); (2) RNA extracted from molar-and gastrolith-forming epithelium from different molt stages (intermolt, early pre-molt, late premolt and post-molt), barcoded and sequenced by 50 bp single-end sequencing (Illumina HiSeq2000, USA); (3) RNA sequenced by 454 technology, as described by Glazer et al (2013); and (4) RNA sequenced 'single pass' by Sanger technology (expressed sequence tags, ESTs) as described by Yudkovski et al (2010). All sequences (also called 'reads') were de novo assembled with CLC Genomics Workbench 6.51 (CLC Bio, Aarhus, Denmark) using default parameters.…”
Section: Temporal and Spatial Transcriptionmentioning
confidence: 99%